La educación financiera y su influencia en las finanzas personales de los ciudadanos de la ciudad de Iquitos, periodo 2020 - Panduro Fernández, Stalin Max (2022)
finances of the citizens of Iquitos, period 2020. The method with a type of investigation with an explanatory level and a quantitative approach, with a non-experimental research design, of a causal correlational cross-sectional type. The population is finite, it was made up of citizens between 18 and 65 years old, from the districts of Iquitos, Punchana, San Juan and Belén and the result of the sample was 260 citizens, being a probabilistic sampling with a stratified random sampling type. The survey technique was applied, and a 23-question questionnaire for the dependent variable personal finance structured in the dimensions: income, expenses, indebtedness and savings using a Gutman scale and the independent variable education was used as an instrument to collect the information. financial, with the dimensions knowledge in budget, financial system, credits, savings and investments by means of a multiple choice answer. The result of the inferential analysis of the first dimension explains that personal finances are weakly influenced by knowledge in budgets, the second dimension explains that personal finances are not influenced by knowledge in the financial system, the third dimension explains that personal finances are weakly influenced by knowledge in debt management and the last dimension explains that personal finances are not influenced by knowledge in savings and investment management. We conclude that there is a very weak positive correlation between the variable financial education and personal finances. That is, with the non-parametric analysis, it can be inferred in the population that financial education influences, but not to a great extent, the reality of personal finances of the citizens of Iquitos.